REINFORCEMENT OF SOCIAL EMOTIONAL EARLY CHILDHOOD IN THE ERA OF SOCIETY 5.0 - Umairi, Mushab Al (Universitas Al-Hikmah Indonesia, 2024)
Early childhood is a time when the foundations are formed for the social and emotional development of a human being. Social emotional ability is a person's ability to manage themselves, be responsible for themselves and others and be able to behave positively when socializing with people around them. The formulation of this research problem discusses the social and emotional strengthening of early childhood education in the era of society 5.0. This research aims to determine the process of providing social emotional reinforcement to early childhood education in the era of society 5.0. The benefit of this research is that adults, both parents and teachers, pay attention to the child's good social emotional development. The type of research used in this research is field research. Then, to obtain data, this research used observation, interviews and documentation methods. This research was analyzed using descriptive qualitative (in the form of opinions or written opinions from people and the actions observed). The conclusion of this research is that providing a good social emotional reinforcement process will have a positive impact on early childhood education in the era of society 5.0. Keywords: Social Emotional, Early Childhood, Era of Society 5.0